Myristica fragrans oil as a potent inhibitor of Candida albicans: Phase development inhibition and synergistic effect - Ratu Juwita Handayani, Irviana Chairunnisa Putri Mahendra, Roshamur Cahyan Forestrania, Aini Gusmira, Robiatul Adawiyah, Anna Rozaliyani, Juliann Nzembi Makau, Muhareva Raekiansyah, Ratika Rahmasari (Journal of Applied Pharmaceutical Science, 2023)
Increasing reports of Candida spp. resistance against azole drugs pressure the need for antifungal discovery with a different mechanism. Myristica fragrans oil has been known to have anti-Candida activity, but its mechanism of action is unknown. To determine the effect of M. fragrans oil on the biofilm development phases of Candida albicans and its combination with fluconazole. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay and quantitative polymerase chain reaction were used to determine the antifungal activity of M. fragrans oil. The time of addition assay was performed at the adhesion, intermediate, and maturation phases. The effect of the combination of M. fragrans oil with fluconazole was determined by the interaction index value. Gas chromatography-mass spectroscopy (GC-MS) was performed to identify potential components. Myristica fragrans oil showed a 50% inhibitory concentration of 1.76% ± 0.4% against C. albicans and also inhibited Candida krusei and Candida glabrata. The time of addition assay showed M. fragrans oil effectively inhibited the adhesion and intermediate phases of biofilm development. The combination with fluconazole produced a synergistic effect. GC-MS indicated the presence of α-copaene (11.47%) and myristicin (11.81%) as the main compounds. Myristica fragrans oil acts on different phases of biofilm development and could be used as an antifungal agent in combination with fluconazole.
Keywords: Myristica fragrans oil, anti- Candida, inhibition phase, combination